A Sequence-Indexed Mutator Insertional Library for Maize Functional Genomics Study . Issue 4 (21st October 2019) - Liang, Lei; Zhou, Ling; Tang, Yuanping; Li, Niankui; Song, Teng; Shao, Wen; Zhang, Ziru; Cai, Peng; Feng, Fan; Ma, Yafei; Yao, Dongsheng; Feng, Yang; et al.
Abstract : A newly developed maize Mutator insertional library named ChinaMu represents the largest sequence-indexed insertional resource for maize to date. Abstract: Sequence-indexed insertional libraries are important resources for functional gene study in model plants. However, the maize ( Zea mays ) UniformMu library covers only 36% of the annotated maize genes. Here, we generated a new sequence-indexed maize Mutator insertional library named ChinaMu through high-throughput sequencing of enriched Mu -tagged sequences. A total of 2, 581 Mu F2 lines were analyzed, and 311, 924 nonredundant Mu insertion sites were obtained. Based on experimental validation, ChinaMu contains about 97, 000 germinal Mu insertions, about twice as many as UniformMu. About two-thirds (66, 565) of the insertions are high-quality germinal insertions (positive rate > 90%), 89.6% of which are located in genic regions. Furthermore, 45.7% (20, 244) of the 44, 300 annotated maize genes are effectively tagged and about two-thirds (13, 425) of these genes harbor multiple insertions. We tested the utility of ChinaMu using pentatricopeptide repeat (PPR) genes. For published PPR genes with defective kernel phenotypes, 17 out of 20 were tagged, 11 of which had the previously reported mutant phenotype. For 16 unstudied PPR genes with both Mu insertions and defective kernel phenotypes, 6 contained insertions that cosegregated with the mutant phenotype. Our sequence-indexed Mu insertional library provides an important resource for functional genomics study in maize.